Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

2207_7579_scan0001.jpg

Grade:11

1 Answers

Saineel Sanjay Prabhudessai
32 Points
11 years ago

For x<0, f(x)= 1+x3. Therefore g(f(x))= g(1+x3)= (1+x3-1)1/3= x.

for x> or =0, f(x)=x2-1. therefore g(f(x))= g(x2-1)=( x2-1+1)1/2= x.

threfore g(f(x))=x for all x belonging to (-infinity,infinity).

 

Thanks,

Saineel.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free